Cyberloafing on Male Employees and Female Employees at PT. Ira Jaya Satria - M. Adly Nabawi; Siti Aisyah (Mahesa Research Center, 2025)
This study aims to determine the differences in cyberloafing between male and female employees at PT. Ira Jaya Satria. The problem is focused on one of the individual factors of cyberloafing, namely gender. The cyberloafing scale in this study was measured based on aspects of cyberloafing, namely; minor cyberloafing, and serious cyberloafing. The scale above uses a Likert scale with 4 answer choices. The sample in this study amounted to 63 people. Data were collected through a sampling technique using a total sampling technique and analyzed quantitatively. This study concludes that based on the results of the T-test Analysis calculation, it is known that there are differences in cyberloafing in terms of gender. This result is known by looking at the value or coefficient of difference with a coefficient of T = 8.646 with p = 0.000 <0.050. Based on these results, it means that the proposed hypothesis which states that there are differences in cyberloafing in terms of gender is declared accepted.